OCCURRENCE OF THE PHENOMENON OF GROWTH COMPENSATION IN INDIAN MAJOR CARPS - Tandon, K K; Johal, M S (Indian Journal of Fisheries, 2011)
The phenomenon of growth compensation is observed in Cirrhina mrigala (Hamilton), Labeo rohita (Hamilton) and Catla catla (Hamilton), in higher age classes from some water bodies of northern India.